Identical RNA-Protein Interactions in Vivo and in Vitro and a Scheme of Folding the Newly Synthesized Proteins by Ribosomes - Das, Debasis (American Society for Biochemistry and Molecular Biology, 2012)
A distinct three-dimensional shape of rRNA inside the ribosome is required for the peptidyl transfer activity of its peptidyltransferase center (PTC). In contrast, even the in vitro transcribed PTC RNA interacts with unfolded protein(s) at about five sites to let them attain their native states. We found that the same set of conserved nucleotides in the PTC interact identically with nascent and chemically unfolded proteins in vivo and in vitro, respectively. The time course of this interaction, difficult to follow in vivo, was observed in vitro. It suggested nucleation of folding of cytosolic globular proteins vectorially from hydrophilic N to hydrophobic C termini, consistent with our discovery of a regular arrangement of cumulative hydrophobic indices of the peptide segments of cytosolic proteins from N to C termini. Based on this observation, we propose a model here for the nucleation of folding of the nascent protein chain by the PTC.